Analysis of Semiotic Found in Football Shoes Advertisements - Widiarta, I Wayan Restu; Devi Maharani Santika, I Dewa Ayu; Eka Pratiwi, Desak Putu (Humanis, 2021)
Aims in this study, first is to find out verbal and non-verbal signs found in football shoes advertisements, and second is to analyze the meaning of verbal and non-verbal signs found in football shoes advertisements. The data sources from this study were taken from the Official Account of Nike, Puma, and Adidas. This study used the descriptive qualitative method. The data were analyzed based on the theory proposed by Saussure (1983) about sign elements, the theory from Barthes (1964) about the meaning of signs, and the supporting theory from Cerrato (2012) to analyze the color terms. The result of this study showed the advertisements used the written texts as the verbal signs and the color choice and picture of advertisements as non-verbal signs. These signs also contained denotative and connotative meanings to make a good combination to attract the attention of readers.